Art of Renaissance Florence a city and its legacy - Nethersole, Scott (Laurence King Publishing, 2019)
In this vivid account Scott Nethersole examines the remarkable period of cultural, artistic and intellectual blossoming in Florence from 1400 to 1520 - the period traditionally known as the Early and High Renaissance. He looks at the city and its art with fresh eyes, presenting the well-known within a wider context of cultural reference. Key works of art - from painting, sculpture and architecture to illuminated manuscripts - by artists such as Michelangelo, Donatello, Botticelli and Brunelleschi are showcased alongside the unexpected and less familiar
Keywords: Geschichte 1400-1520; Kunst; Florenz; Art, Renaissance / Italy / Florence; Painting, Renaissance / Italy / Florence; Architecture, Renaissance / Italy / Florence; Architecture, Renaissance; Art, Renaissance; Italy / Florence